Signs and Staging of Breast Cancer at Diagnosis During Active Conflict in Northwest Syria - Mutair, Yahya; Al-Daoud, Fouad; Mushtaq, Gohar; Hariri, Mahmoud (Journal of medical and pharmaceutical sciences, 2024)
Objective: : To study the clinical signs of patients with breast cancer in northwestern Syria and determine the type of breast cancer and the clinical stage at diagnosis. Methodology: This prospective study included 39 patients attending the General Surgery Clinic at Idlib University Hospital between 2021 and 2023. Data were collected using a special form. All patients underwent a triple breast Assessment ( History and clinical examination radiological investigations, biopsy), followed by the appropriate surgical procedure and histological examination of the resected specimen postoperatively. Results: : The average age of patients with breast cancer was 48.6 ± 13.77 years, with ages ranging from 24 to 83 years. Physical examination revealed that all patients had a palpable breast mass, with an average tumor size of 29 ± 13.38 mm. Histologically, 98% of the diagnosed breast cancer cases were invasive carcinomas, and 2% were in situ carcinomas. Regarding the type of cancer, 76.9% were invasive ductal carcinomas (IDC), 12.8% were invasive lobular carcinomas (ILC), 2.6% were mucinous carcinomas (MC), and 2.6% were mixed ductal and lobular carcinomas (IDC+ILC). The tumor grade of 61.5% of patients was Grade II. Histopathological results showed that 48.7% of patients were in the early stage, and 51.3% were in the late stages of the disease. Conclusion: Breast cancer in northwestern Syria affects both males and females, Among the affected individuals, 94.9% were women (37 cases) and 5.1% were men (2 cases) with most patients presenting in advanced stages and experiencing late symptoms and signs. Therefore, there is an urgent need to promote self-breast examination skills and implement screening programs for early detection, which should be endorsed by local health authorities.